Craniospinal Anomalies and their Management - Huma Mushtaq (Journal of Rawalpindi Medical College, 2015)
Background : To find out the frequency of various craniospinal anomalies and their management in Rawalpindi Methods: In this cross sectional study patients with congenital gross craniospinal anomalies, were included. All patients were assessed from head to toe for any other associated anomalies. . Patients with high neural tube defects, cases associated with other gross anomalies and children below 15 days of age were deferred for operation. Patients with craniospinal anomalies were advised for CT scan brain and Spinal X ray. In Hydrocephalus patient’s ventricular tap was performed and CSF was sent for routine examination before inserting ventriculo-peritoneal shunt. Patients who were expected to have adequate quality of life and with amenable neural tube defects were operated after proper investigations. Results: A total number of 160 cases of craniospinal anomalies were presented . Majority of the cases were males (57%). The most common anomaly observed was of hydrocephalus (66.25%) and second most common anomaly was of myelomeningocele (14.37%). There were 2 cases of anencephaly, which were managed conservatively because of their incompatibility with life. Majority of the cases of hydrocephalus were operated on priority basis to restrict their head size. Cases of hydrocephalus which presented in patients above 6 months of age and with enlarged 3rd ventricle underwent 3rd ventriculostomy while others underwent shunting procedure. Conclusion: Patients presenting with high neural tube defects and have systemic congenital defects should be treated by non-operative measures. Patients presenting with amenable neural tube defect and who are expected to have adequate quality of life should be given proper surgical treatment along with proper counseling.